Low-Grade Inflammation and Muscular Fitness on Insulin Resistance in Adolescents: Results from Labmed Physical Activity Study - Garcia-Hermoso, A (Blackwell Publishing Ltd, 2018)
Background: Low muscular fitness (MF) and low-grade inflammation has been linked to insulin resistance (IR). Objective: To evaluate the associations between MF and a clustered score of inflammatory biomarkers on IR and to investigate the combined impact of MF and inflammation on IR in adolescents. Methods: This is a cross-sectional analysis with 529 adolescents (267 girls) aged 12 to 18 years. Pubertal stage, socioeconomic status, adherence to the Mediterranean diet, cardiorespiratory fitness, and waist circumference were assessed. Standing long-jump and isometric handgrip dynamometry were used as indicators of MF. Continuous score of clustered inflammatory biomarkers (InflaScore) (sum of Z-scores of C-reactive protein, C3, C4, fibrinogen, and leptin) and IR (homeostasis model assessment of insulin resistance [HOMA-IR] estimated from fasting serum insulin and glucose) were assessed. Results: HOMA-IR and fasting insulin were positively associated with InflaScore and negatively associated with MF, independently of age, sex, pubertal stage, socioeconomic status, adherence to the Mediterranean diet, cardiorespiratory fitness, and waist circumference. Adolescents classified as High InflaScore/Unfit showed significantly higher HOMA-IR when compared than those with High InflaScore/Fit and those with Low InflaScore/Fit (F(3,519) = 4.761, P <.003), after adjustments for potential confounders. Unfit adolescents with high InflaScore had the highest odds of expressing high HOMA-IR (odds ratio, OR = 2.40, 95% confidence interval [CI]: 1.2-5.6) and insulin risk (2.53 95% CI, 1.5-5.9) when compared to those of the Low InflaScore/Fit group, after adjustments for potential confounders. Conclusion: Higher levels of MF seem to minimize the deleterious effect of inflammation on IR. © 2017 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd